Evaluación del rendimiento operacional en la bajada de tubería para un taladro de workover. (2023)
The operations of lowering the pipe to the well are one of the most important procedures for the Workover equipment, because their execution times within the well program represent a large percentage; In addition, these operations make the most of the equipment components, being one of the main causes of wear, damage to equipment and risks to personnel, in addition to having direct consequences with the cost of operations.